(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to elucidate the theoretical concepts related to the research variables, which include strategic auditing and its dimensions (strategic planning, operational performance, governance, compliance program, strategic performance evaluation, auditor independence) and the variable of credit risk in banking within the surveyed Iraqi private commercial banks. The research was applied to several banks, namely: Al Ahli Iraqi Bank, Gulf Commercial Bank, Mansour Investment Bank, and Ashur International Investment Bank. The descriptive analytical approach was adopted using a questionnaire distributed to a sample of 120 officials out of a total population of 125, comprising individuals in senior, middle, and executive management levels. The statistical program (SPSS) was utilized to calculate the mean, standard deviation, Pearson correlation coefficient, and simple linear regression test. The research concluded with several findings, the most significant of which is the existence of a significant impact and correlation between strategic auditing and credit risk in banking. This indicates that institutions relying on strategic auditing as an effective control tool are better equipped to manage credit risks, thereby contributing to the enhancement of financial and administrative stability.